19th-century anatomical illustration: Part one - A portfolio of selected early 19th-century anatomical works - Grzegorz Wysiadecki; Ivan Varga; Ilona Klejbor; Krzysztof Balawender; Sanjib Kumar Ghosh; Edward Clarke; Małgorzata Mazur; Wojciech Przybycień; Andrzej Dubrowski; Michał Bonczar; Patryk Ostrowski; Justyna Rdzanek; et al. (Elsevier, 2024)
Background: Since the appearance of Vesalius's treatises, anatomical illustration has eluded unified conventions and strictly defined timeframes, resulting from the individual struggles of scholars and collaborating artists. Until the 19th century, diverse styles characterized anatomical illustrations, and the conventions in which they were created depended on both by cultural conditions and the state of knowledge about the structure of the human body. Aim: This paper presents selected illustrated anatomical sources published in the early 19th century. Conclusions: In early 19th-century anatomical iconography, there was a trend of deepening the importance of scientific illustration as a carrier of information and knowledge. Illustrations from this period are still characterized by various styles, degrees of scientific precision, and the scope of detail presented. However, during this period, attempts were made to faithfully reflect the reality of the dissecting room and the anatomical specimen.